Advances in nanotechnology for the therapy of bacterial pneumonia - Zihan Tian; Zihan Tian; Yuwei Zhang; Jiachen Yun; Weihong Kuang; Weihong Kuang; Jin Li (Frontiers in Cellular and Infection Microbiology)
Bacterial pneumonia, a life-threatening infection, is the world’s sixth deadliest disease and the top cause of mortality in children under five. Without timely treatment, bacterial pneumonia can escalate to a 30% mortality rate, particularly in high-risk populations. It may also lead to chronic conditions such as pulmonary fibrosis and chronic obstructive pulmonary disease(COPD), along with systemic inflammatory responses that can progress to sepsis and multi-organ failure. Although antibiotics are generally effective against bacterial pneumonia, current treatment approaches remain insufficient due to several barriers, including the lung’s unique mucus barrier, low pH, high oxidative stress, disruption of alveolar surfactants, and accumulation of hypertonic fluid on the airway surface. In addition, following the excessive use of antibiotics, dysbiosis, secondary infections and resistance occur. Nanomaterials can be an effective way to improve therapeutic effects owing to their change on drug size, physicochemical properties, hydrophobicity along with better targeting ability, and controlled localized release. Organic and inorganic substances and their composites are the three main types of nanomaterials to treat bacterial pneumonia. This review presents the latest advancements and constraints of these nanomaterials from a nanotechnology viewpoint with a view to developing therapeutic strategies for bacterial pneumonia.